The Educational Epistemology Of Traditional Pesantren - Ahmad Sulton (TADRIS: Jurnal Pendidikan Islam, 2022)
This study aims to explore the reasons al-Maqbul pesantren maintains the traditional education system in the educational epistemology perspective. This research is qualitative, describe data obtained from the field and literature related to the discussion. To get the data used data collection techniques through observation, interviews and documentation. This study resulted in the findings, namely: (1) The reason al-Maqbul pesantren maintains the traditional education system cannot be separated from the epistemological construction of education; (2) The influence of the epistemological foundation of education at the al-Maqbul pesantren on its educational goals can be identified from Bayani's tendency to place sources of knowledge instead of logical reasoning, empirical observations, and scientific methods. However, the texts of the Qur'an, Hadith, and the Yellow Book; (3) According to the view of al-Maqbul pesantren, truth, knowledge, and educational methods are obtained from the texts of the Qur'an, Hadith, and the Yellow Book. The conclusion of this study is that al-Maqbul pesantren still maintains the purity of its original identity as a place to study religious sciences for its students. All knowledge learned in this pesantren is entirely religious in nature, sourced from Arabic-language books, does not include general knowledge in the education system.